Effect of interferon-α on cortical glutamate in patients with hepatitis C: a proton magnetic resonance spectroscopy study. Issue 4 (10th May 2013) - Taylor, M. J.; Godlewska, B.; Near, J.; Christmas, D.; Potokar, J.; Collier, J.; Klenerman, P.; Barnes, E.; Cowen, P. J.
Abstract : Background: The development of depressive symptomatology is a recognized complication of treatment with the cytokine interferon- α (IFN- α ) and has been seen as supporting inflammatory theories of the pathophysiology of major depression. Major depression has been associated with changes in glutamatergic activity and recent formulations of IFN-induced depression have implicated neurotoxic influences that could also lead to changes in glutamate function. The present study used magnetic resonance spectroscopy (MRS) to measure glutamate and its major metabolite glutamine in patients with hepatitis C who received treatment with pegylated IFN- α and ribavirin. Method: MRS measurements of glutamate and glutamine were taken from a 25 × 20 × 20 mm voxel including the pregenual anterior cingulate cortex in 12 patients before and after 4–6 weeks of treatment with IFN. Results: IFN treatment led to an increase in cortical levels of glutamine ( p = 0.02) and a significant elevation in the ratio of glutamine to glutamate ( p < 0.01). Furthermore, changes in glutamine level correlated significantly with ratings of depression and anxiety at the time of the second scan. Conclusions: We conclude that treatment with IFN- α is associated with MRS-visible changes in glutamatergic metabolism. However, the changes seen differ from those reported in major depression, which suggests that the pathophysiology of IFN-induced depression may be distinct from that of major depression more generally.